IMPLEMENTATION OF THE SYNERGY OF TRANSFORMATIONAL-SERVANT LEADERSHIP CHARACTER IN ISLAMIC BOARDING SCHOOL - Helmi Muhammad; Niki Puspita Sari (Journal of Leadership in Organizations, 2021)
Introduction/Main Objectives: This research examined the synergy of transformational and servant leadership character, which was suitable for Islamic boarding schools' perspective as an Islamic typology. Background Problems: The study of transformational and servant leadership has only focused on the business sector from a western perspective, which tends to be productivity-oriented. Meanwhile, the spirit of the two leadership characters is on morals and human, which have never been reviewed in empirical studies, especially in the perspective of Islam and in the context of Islamic boarding schools. Novelty: The synergy of transformational and servant leadership formed a new model which was inclusive perspective leadership of Islamic boarding school. Research Methods: This research used single case study approach with an exploratory descriptive design. Data collection was done by in-depth interviews with several informants who were selected purposively and through snowball sampling. The data were analyzed by using interactive models. Finding/Results: The results showed that the conformity of transformational and servant leadership could be implemented in the leadership in Islamic boarding schools. The leader of the Islamic boarding school can be a transformational leader as well as a serving leader. Islamic boarding school as an organization has a mission of change in the context of transformational leadership with modes of serving in the context of servant leadership. The synergy of these characters could potentially be an inclusive leadership model. Conclusion: The two models of leadership must be used simultaneously in leadership in Islamic boarding schools. The resulting combination will manifest the message of the mercy of Islamic leadership.